Taman Wisata Mangrove dan Budidaya Ikan Kota Kendal - Sari, Ratih Evi Purnama; , Rini Hidayati, ST, MT (2016)
Mangrove tourism park and fish cultivation center in Kendal is a tourism area that has variety of plant within tidal region equipped by fish cultivation business/ activities. This area exploits its natural resources both in natural or cultivation condition. In order to achieve a good result on designing Kendal Mangrove Tourism Park and Fish Cultivation Center, which gives more profit for the society and surrounding, some methods through observation, literature study, data processing, and data analysis are used. The purpose behind the design of Kendal Mangrove Tourism Park and Fish Cultivation Center is to provide information and knowledge. It is also used for conservation and tourist destination without significantly ruining the environment around the park. The area regulation has been set using eco friendly approach to achieve a good design. The design of Kendal Mangrove Tourism Park and Fish Cultivation Center is wrapped in educative and recreational way. Furthermore, it is believed that the visitors are not just having vacation but also given useful information on how important mangrove is to protect them from abrasion.